2017
DOI: 10.1039/c6tx00410e
|View full text |Cite
|
Sign up to set email alerts
|

The UCP2-related mitochondrial pathway participates in rhein-induced apoptosis in HK-2 cells

Abstract: Rhein is one of the main active compounds in total rhubarb anthraquinones (TRAs) that were reported to cause nephrotoxicity. This paper explored the mechanism of how rhein induced apoptosis in human renal proximal tubular epithelial cells (HK-2 cells). In this study, rhein was found to induce apoptosis in HK-2 cells according to the results of annexin V/PI staining assay. The underlying mechanisms were investigated, and the mitochondria-mediated pathway was found to be critical. A series of related biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Rhein also induced toxicity at the dosage of 6.25-50 µM in hepatocytes in vitro [185]. In another investigation, it was observed that rhein induced apoptosis in renal epithelial HK-2 cells through the uncoupling protein (UCP)-2-related mitochondrial pathway [186]. In addition, the dose-dependent effects of rhein exerted a toxic effect in hepatic HL-7702 cells via the oxidative stress-involved mitochondria-mediated apoptotic pathway.…”
Section: Toxicity Of Rheinmentioning
confidence: 99%
“…Rhein also induced toxicity at the dosage of 6.25-50 µM in hepatocytes in vitro [185]. In another investigation, it was observed that rhein induced apoptosis in renal epithelial HK-2 cells through the uncoupling protein (UCP)-2-related mitochondrial pathway [186]. In addition, the dose-dependent effects of rhein exerted a toxic effect in hepatic HL-7702 cells via the oxidative stress-involved mitochondria-mediated apoptotic pathway.…”
Section: Toxicity Of Rheinmentioning
confidence: 99%
“…In this paper, we demonstrated that the cytotoxicity of AA I was caused via apoptosis by Hoechst 33,258 staining and caspase-3. Cell apoptosis is accompanied by various morphological changes, including nuclear condensation, apoptotic bodies and DNA fragmentation [ 34 , 35 ], which was analyzed using Hoechst 33,258 staining ( Figure 2 B). Caspases are among the best characterized biochemical markers for apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The intensity of fluorescence reasoned is proportional to the amount of hydrogen peroxide generated by the cells (Wang & Youle, 2009). Briefly, 5 × 10 5 cells/well exposed to astrakurkurol for 24 hr and as described by Mao et al, 2017, the…”
Section: Detection Of Intracellular Levels Of Rosmentioning
confidence: 99%